The state of legislation and policy protecting Australia's mangrove and salt marsh and their ecosystem services. (October 2016) - Rogers, Kerrylee; Boon, Paul I.; Branigan, Simon; Duke, Norman C.; Field, Colin D.; Fitzsimons, James A.; Kirkman, Hugh; Mackenzie, Jock R.; Saintilan, Neil
Abstract: Saline coastal wetlands, such as mangrove and coastal salt marsh, provide many ecosystem services. In Australia, large areas have been lost since European colonization, particularly as a result of drainage, infilling and flood-mitigation works, often starting in the mid-19th century and aimed primarily towards converting land to agricultural, urban or industrial uses. These threats remain ongoing, and will be exacerbated by rapid population growth and climate change in the 21st century. Establishing the effect of wetland loss on the delivery of ecosystem services is confounded by the absence of a nationally consistent approach to mapping wetlands and defining the boundaries of different types of coastal wetland. In addition, climate change and its projected effect on mangrove and salt marsh distribution and ecosystem services is poorly, if at all, acknowledged in existing legislation and policy. Intensifying climate change means that there is little time to be complacent; indeed, there is an urgent need for proper valuation of ecosystem services and explicit recognition of ecosystem services within policy and legislation. Seven actions are identified that could improve protection of coastal wetlands and the ecosystem services they provide, including benchmarking and improving coastal wetland extent and health, reducing complexity and inconsistency in governance arrangements, and facilitating wetland adaptation and ecosystem service delivery using a range of relevant mechanisms. Actions that build upon the momentum to mitigate climate change by sequestering carbon – 'blue carbon' – could achieve multiple desirable objectives, including climate-change mitigation and adaptation, floodplain rehabilitation and habitat protection. Graphical abstract: Highlights: Human and climate-induced changes will cause coastal wetlands to migrate and change. Effectiveness of wetland management may be affected by spatio-temporal changes in extent A review of Australian coastal management policy that could be affected is provided The capacity of existing policy to effectively improve ecosystem outcomes is explored. Actions that will improve the fate of coastal wetlands and their ecosystem services are provided.